Lamina Cribrosa Visibility Using Optical Coherence Tomography: Comparison of Devices and Effects of Image Enhancement Techniques - Girard, M. J. A.; Tun, T. A.; Husain, R.; Acharyya, S.; Haaland, B. A.; Wei, X.; Mari, J. M.; Perera, S. A.; Baskaran, M.; Aung, T.; Strouthidis, N. G. (Investigative ophthalmology & visual science, 2015)
To compare the visibility of the lamina cribrosa (LC) in optic disc images acquired from 60 glaucoma and 60 control subjects using three optical coherence tomography (OCT) devices, with and without enhanced depth imaging (EDI) and adaptive compensation (AC). A horizontal B-scan was acquired through the center of the disc using two spectral-domain (Spectralis and Cirrus; with and without EDI) and a swept-source (DRI) OCT. Adaptive compensation was applied post acquisition to improve image quality. To assess LC visibility, four masked observers graded the 1200 images in a randomized sequence. The anterior LC was graded from 0 to 4, the LC insertions from 0 to 2, and the posterior LC either 0 or 1. The effect of EDI, AC, glaucoma severity, and other clinical/demographic factors on LC visibility was assessed using generalized estimating equations. The anterior LC was the most detectable feature, followed by the LC insertions. Adaptive compensation improved anterior LC visibility independent of EDI. Cirrus+EDI+AC generated the greatest anterior LC visibility grades (2.79/4). For LC insertions visibility, DRI+AC was the best method (1.10/2). Visibility of the posterior LC was consistently poor. Neither glaucoma severity nor clinical/demographic factors consistently affected LC visibility. Adaptive compensation is superior to EDI in improving LC visibility. Visibility of the posterior LC remains poor suggesting impracticality in using LC thickness as a glaucoma biomarker.